(untitled) (Journal of Applied Membrane Science & Technology, 2018)
Hydrophilic membranes exhibit good flux and low fouling tendency, which are the crucial criteria for a good membrane.Â Attempts have been done by researchers over the past decades to enhance the hydrophilicity of membrane by using nanoparticles and grafting. However, these processes are tedious and costly. This study improves the hydrophilicity of cellulose acetate (CA) membranes by using ethylenediaminetetraacetic acid (EDTA) via simple blending method. Recent study showed that fouled membrane which was cleaned by EDTA exhibited high water flux performance. However, the use of EDTA in formulating a membrane has not been disclosed elsewhere. Thus, the objective of this study is to conduct a series of experiments to find out the role of EDTA in improving the hydrophilicity of CA membranes. Membranes with varying EDTA concentration were prepared via dry-wet phase inversion technique. Contact angle, porosity and water flux of the resultant membranes were determined. Additionally, the morphologies of the membranes were imaged using FESEM. Results showed that EDTA was a good pore former, which can be seen clearly from FESEM images. This explains for the high porosity properties in CA-EDTA membranes.Â Membrane with 1 wt% of EDTA showed the highest water flux, which was 15 L/(h.m2). Meanwhile, no water flux was observed after three hours when pure CA membrane was used in a dead-end filtration cell. In conclusion, EDTA is a promising additive in improving the hydrophilicity of membranes.